2022
DOI: 10.1186/s12884-022-04658-3
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Perinatal Depression Risk among internally displaced Yazidi Women in Iraq: a descriptive cross-sectional study

Abstract: Background Yazidi survivors of a 2014 genocidal attack by the self-proclaimed Islamic State of Iraq and Syria (ISIS) have complex medical and mental health needs in the perinatal and postpartum period. Few studies have assessed perinatal mental health needs for this population of women who are living in camps for Internally Displaced Persons (IDP) in the Kurdistan Region of Iraq (KRI). Methods The specific aim of this formative cross-sectional stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Among obstetric history, the result of these study revealed that experience of abortion and gender of baby were risk factors of antenatal depression. This result of the current study supported by Seidi A et.al., (2022) (47) and Shidhaye P et al, (2017) (46) . Furthermore, the risk factors of stress which reported by this study were age of marriage, sleeping hours at night, health problems associated previous pregnancy, post-partum complications and type of pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…Among obstetric history, the result of these study revealed that experience of abortion and gender of baby were risk factors of antenatal depression. This result of the current study supported by Seidi A et.al., (2022) (47) and Shidhaye P et al, (2017) (46) . Furthermore, the risk factors of stress which reported by this study were age of marriage, sleeping hours at night, health problems associated previous pregnancy, post-partum complications and type of pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…2019) or displaced persons (Seidi et al . 2022) to mention some diverse examples. A woman's mental health presentation in the perinatal period may be distinct when compared to any other time in the lifecycle.…”
Section: Implications For Future Directions In Mental Health Nursingmentioning
confidence: 99%
“…This work is often in specialist settings. Nursing input extends to almost all care contexts, however, be it rural mental health care (Hine et al 2016), perinatal crisis intervention during intensive home treatment (Rubio et al 2021), forensic perinatal mental health (Dolan et al 2019) or displaced persons (Seidi et al 2022) to mention some diverse examples. A woman's mental health presentation in the perinatal period may be distinct when compared to any other time in the lifecycle.…”
Section: Implications For Future Direc-tions In Mental Health Nursingmentioning
confidence: 99%
“…These experiences have been differentiated with regard to the 'antenatal' and 'postnatal' time periods, or both [18]. Some of the Collection papers refer specifically to the adverse experiences of pregnancy loss or bereavement [19], domestic violence [20] or being displaced during genocidal violence [21].…”
Section: Issues Of Definitionmentioning
confidence: 99%